(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Trust plays a crucial role in shaping consumer behavior within food systems, particularly in the context of local meat supply chains where concerns over food safety, authenticity, and sustainability are growing. This study investigates the relationship between consumer trust and willingness to pay (WTP) for locally produced meat in Malaysia, aiming to assess how trust in locality, quality, safety, labeling, certificate and packaging for local meat influences consumer purchasing decisions and willingness to pay. Using a Contingent Valuation Method (CVM), a Double Bounded Dichotomous Choice (DBDC) model was used to analyse an econometric model and survey data among 292 respondents. The analysis explores demographic and technical determinants of trust and WTP while considering price sensitivity factors unique to the Malaysian context. Certificate and packaging are statistically significant with WTP, and it reveal that consumers’ WTP at RM28.88. By advancing understanding of consumer behavior in emerging markets, this study contributes to the development of resilient and sustainable food systems aligned with Malaysia’s broader food security and environmental goals. These insights contribute to the development of resilient and sustainable food systems in Malaysia, encouraging trust-based purchasing.